Consumer Attitude toward Purchase Intention of Culinary Product’s through Video-Based Social Media: A Deductive Exploratory Studies in Bandung City - Ahmad, Lukni Burhanuddin; Septiarini, Eka; Satriawan, Dhennies Ariel Aru; Aas, Raihan Elian (The Asian Journal of Technology Management (AJTM), 2023)
In today's digitalization era, promoting products using social media has become the primary strategy to accelerate business growth, especially promotion. With the emergence of various short video-based social media platforms, information can rapidly spread through a solid and short video duration. For many content creators, a short video can call crowds faster than other types of data transmissions, such as text, pictures, or traditional video. Millions of views can be gained in a matter of days. The video that gains high exposure is not always because of the celebrity or famous person; it is more of the quality of the content itself. One of the most popular themes is related to culinary products. Bandung, recognized as a city of culinary in Indonesia, has many content creators that create food promotional videos. Some of them have millions of followers that advocate for their followers to try and purchase the food. This phenomenon raises questions to be revealed, becoming the background for this research. This study aimed to determine the variables causing interest in purchasing culinary products in Bandung through Short Video-Based Social Media. Thus, this study contributes to theory development, business practice, and digital marketing through short videos posted on various social media platforms. The method used in this research is deductive exploratory research as a methodological approach that investigates the micro-conceptual framework of working hypotheses that have not been studied in-depth with qualitative data collection techniques using data collection techniques with in-depth interviews (IDI) and focus group discussions (FGD). Online to specific individuals and groups. As a result, seven of eight factors are considered to independently influence intention to purchase culinary products towards SVBSM by the respondents: perceived ease of use, perceived usefulness, consumer personality characteristics, retail, commercial images, product features, attractiveness, and trustworthiness.